2021
DOI: 10.3389/fonc.2021.744107
|View full text |Cite
|
Sign up to set email alerts
|

CD146 as a Prognostic-Related Biomarker in ccRCC Correlating With Immune Infiltrates

Abstract: BackgroundsCD146 is highly expressed in various malignant tumors and associated with the poor prognosis. However, the role of CD146 in clear cell renal cell carcinoma (ccRCC) is still unknown. This study aimed to identify the role of CD146 in ccRCC by integrated bioinformatics analysis.MethodsCD146 mRNA expression and methylation data in ccRCC was examined using the TIMER, UALCAN, and MethSurv databases. CD146 expression in paraffin-embedded tissues (140 cancer samples and 140 paracancer tissues) from our coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…NEK2, NIMA-related kinase 2, was found to be overexpressed in ccRCC and high expression of NEK2 was associated with a poor prognosis [ 56 ]. CD146 was identified to be elevated in ccRCC tissues, and high CD146 expression was associated with poor prognosis in patients with ccRCC [ 57 ]. FGL1, fibrinogen-like protein 1, which is known as a novel potential immune checkpoint target [ 58 ], was recognized to be upregulated in tumor tissues and plasma specimens of ccRCC patients, and high FGL1 expression predicted a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…NEK2, NIMA-related kinase 2, was found to be overexpressed in ccRCC and high expression of NEK2 was associated with a poor prognosis [ 56 ]. CD146 was identified to be elevated in ccRCC tissues, and high CD146 expression was associated with poor prognosis in patients with ccRCC [ 57 ]. FGL1, fibrinogen-like protein 1, which is known as a novel potential immune checkpoint target [ 58 ], was recognized to be upregulated in tumor tissues and plasma specimens of ccRCC patients, and high FGL1 expression predicted a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the insensitivity of renal clear cell carcinoma to radiotherapy and chemotherapy, surgical operation is still the dominant treatment method, although the postoperative recurrence rate is still nearly 40%. In recent years, immunotherapy-based combinations have become the standard of treatment for patients with metastatic RCC and have shown effectiveness and improved overall survival in the first-line metastatic scenario ( Lv et al, 2021 ). As a heterogeneous disease, ccRCC still lacks effective biomarkers for individualized treatment methods, especially in current immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TAM can promote tumor proliferation, angiogenesis, and metastasis ( 35 ). Recent research has demonstrated that an inflammatory environment can promote the occurrence and development of tumors ( 21 ). Therefore, we speculated that AQP5 expression promoted the generation and accelerated PAAD progression.…”
Section: Discussionmentioning
confidence: 99%
“…The normal pancreatic tissues of PAAD patients were obtained from Xijing Hospital. Western blotting, RT-PCR, immunofluorescence, and immunohistochemistry were performed as previously reported ( 21 – 23 ). The following antibodies were used: AQP5 (Abcam, Ab92320) and tubulin (Proteintech, 10094-1-AP).…”
Section: Methodsmentioning
confidence: 99%